Asymptomatic cardiac manifestations in CKD - L. S., Adarsh; Reddy, Sravanthi; Shetty, Manjunath S. (International Journal of Research in Medical Sciences, 2018)
Background: Chronic kidney disease is recognised as health concern globally with more than 40 percent of morbididty and mortality. CKD is one of the independent risk factor for cardiovascular diseases and its unfavourable health outcomes. The risk factors like smoking, hypertension, dyslipidemia and diabetes which are highly prevalent in CKD. The therapeutic interventions in CKD patients to reduce CVD events does not hold a desired effect and has bad prognosis in end stage renal disease. The initial evidence indicating a relationship between CKD and CVD is more apparent in patient with dialysis. The aim of the study was to evaluate the asymptomatic cardiac manifestations in 2-4 stages of CKD through non-invasive methods like ECG and Echocardiography. Methods: It is a cross sectional study investigated on 250 CKD patients receiving care in JSS hospital, Mysore. For the primary objective, correlational analysis were performed to evaluate the association of renal functional parameters like serum creatinine, urine albumin, eGFR with cardiac parameters through ECG and Echocardiographic changes. Results: ECG revealed LVH with pressure overload pattern in 36%. 25% patients had ST-T changes. Echocardiography revealed LVH and diastolic dysfunction as abnormalities. LVH has significant p value. Conclusions: CVD is a leading cause of morbidity and mortality in patients of CKD who succumb to Cardio vascular deaths before reaching the end stage renal disease. Thus, focus of patient care in early CKD stages should be directed to prevention of cardiovascular complications through early ECG and Echocardiography.